2007
DOI: 10.1159/000099344
|View full text |Cite
|
Sign up to set email alerts
|

Adult Male Circumcision Outcomes: Experience in a Developing Country Setting

Abstract: Introduction: We examined male circumcision outcomes among young adults in an African setting. Materials and Methods: Participants were healthy, sexually active, uncircumcised, HIV-seronegative males aged 18–24 years. The main outcomes measured included complications, healing, satisfaction and resumption of activities. Results: Of 1,475 procedures, 26 (1.8%) were associated with 27 adverse events, most commonly wound disruption/delayed healing (0.6%), wound infection (0.4%), and bleeding (0.3%). Adverse events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 27 publications
4
40
1
Order By: Relevance
“…RCTs have shown that more experienced providers perform faster and safer circumcisions, 8,22 and our results confirm these findings. In our study, the providers who had performed only 20 male circumcisions under supervision took an average of 21.0 minutes to perform their first 20 procedures; however, providers who had performed more than 100 circumcisions and those who had performed over 200 procedures took an average of 17.6 and 15.5 minutes, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…RCTs have shown that more experienced providers perform faster and safer circumcisions, 8,22 and our results confirm these findings. In our study, the providers who had performed only 20 male circumcisions under supervision took an average of 21.0 minutes to perform their first 20 procedures; however, providers who had performed more than 100 circumcisions and those who had performed over 200 procedures took an average of 17.6 and 15.5 minutes, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…This study lends support to recommendations that providers must perform a minimum of 20 male circumcision procedures to qualify as a VMMC provider, and ideally over 100 procedures to reach and maintain a desired level of clinical expertise. 8,22 In Kenya, legislation was passed in 2009 to allow nurses to provide VMMC services as part of the national VMMC programme. While adjusting for provider experience reduced the magnitude of the protective effect conferred by having a clinician rather than a nurse perform the circumcision, in the clinic system a procedure performed by a clinician was still 40.0% less likely to result in an adverse event than one performed by a nurse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reduced to <1% after 400 circumcisions. (126) Fictions Various myths abound concerning circumcision. Emotive arguments, such as ones prevalent on anti-circumcision internet sites, are not supported by current scientific evidence.…”
Section: Complicationsmentioning
confidence: 99%
“…Unless combined with other surgery, circumcision later obviously requires a separate (occasionally overnight) visit to hospital. Healing is slower than in newborns and the rate of complications is greater, but still low: 1-4% (Auvert et al, 2005;Cathcart et al, 2006;Bailey et al, 2007;Gray et al, 2007;Krieger et al, 2007). Most common is postoperative bleeding (0.4-0.8%), infection (0.2-0.4%), wound disruptions (0.3%), problems with appearance (0.6%), damage to the penis (0.3%), insufficient skin removed (0.3%), delayed wound healing (0.1%), delayed healing (0.2%), swelling at the incision site or haematoma (0.1-0.6%) or need to return to the theatre (0.5%).…”
Section: Freehand Methodsmentioning
confidence: 99%